HUBUNGAN GERAKAN RUKUK SAAT SHOLAT DENGAN FLEKSIBILITAS HAMSTRING DI MASJID AL BAROKAH CIMAHI - Mohammad Ali; Feisal Reinardy; Andy Martahan Andreas H (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
The bow movement, keeping the coccygeal bone attached to the spine, improve blood circulation from the heart to the rest of the body, Avoid various diseases of the spine. This movement is useful for maintaining the perfect position and function of the spine (corpus vertebrae) as a support for the body and nerve center. In the bow movement there is a concentric hamstring muscle contraction and after the bow there is a contraction of the excentric muscles. Good muscle flexibility is determined by the muscle's ability to generate maximum strength through eccentric and concentric contractions. The purpose of this study was to determine the relationship between hamstring flexibility and bowing movements in the congregation of Al-barokah Mosque in Cimahi. This study used an analytical observational research method, a sample of 100 worshipers with the sampling technique was purposive sampling. Data analysis used univariate and bivariate analysis. The results showed that the hamstring flexibility of the congregation at Masjid Al Barokah Cimahi was mostly in the excellent criteria and most of the prostration movements during prayer were done correctly. The results of this study indicate that there is a relationship between hamstring flexibility and prostration movements. So that the flexibility of this hamstring has an important role in the movement of prostration during proper prayer.